Determinants of Savings Rate in Rural Nigeria: A Micro Study of Kwara State (2013)
The inability of households to save over time has significant influence on the rate of capital accumulation and economic growth in developing countries. In order to understand this trend, this research assesses savings rates and its correlates in rural Kwara state, Nigeria. A multi- stage sampling procedure was used to obtain data from 120 households. This was then analyzed using two descriptive statistics: the generalized linear model and the Tobit regression model. Results show that majority of the rural households were male-headed (81.0 percent) and combined farming with other non-farming activities (73.5 percent). The Tobit regression model reveals that age squared (p< 0.10) and diversification of non- farming activities (p< ) and diversification of non- farming activities (p<0.05) positively influence rural saving rates.